Comparison of Efficacy of Terlipressin Versus Octreotide in Management of Acute Variceal Hemorrhage - Butt, Ramza Naeem; Hussain, Murtaza; Hussain, Maria; Yousaf, Haroon; Akram, Samahir; Ijaz, Shanza (Biological and Clinical Sciences Research Journal, 2025)
Acute oesophageal variceal bleeding is a life-threatening complication of liver cirrhosis requiring urgent medical intervention. Terlipressin and octreotide are commonly used pharmacologic agents, but comparative data on their efficacy in achieving haemostasis prior to endoscopic intervention remain inconclusive. Objective: To compare the efficacy of terlipressin and octreotide in controlling bleeding in cirrhotic patients with acute variceal haemorrhage during the pre-endoscopic period. Methods: This prospective observational cohort study was conducted over three months January to March, 2025 at the Department of Internal Medicine, Shalamar Hospital, Lahore. A total of 114 patients with cirrhosis and acute variceal bleeding were included, with 57 patients receiving terlipressin and 57 receiving octreotide based on physician preference. The primary outcome was pre-endoscopic hemostasis, defined by clinical and endoscopic criteria. Baseline demographics, bleeding control rates, and hospital stay durations were analyzed. Results: The mean age of participants was 51.6 ± 7 years, with 71.8% being male. The most common etiology of cirrhosis was hepatitis C (55%). Bleeding control was achieved in 88% of patients in the terlipressin group and 85% in the octreotide group (p = 0.787). The average length of hospital stay was 5.61 days for the terlipressin group and 5.21 days for the octreotide group (p = 0.395), with no significant difference between the two. Conclusion: Both terlipressin and octreotide are effective in achieving pre-endoscopic haemostasis in patients with acute variceal bleeding. While terlipressin showed a slightly higher success rate, the difference was not statistically significant. Either agent can be considered in emergency settings, particularly when endoscopy is delayed or unavailable.